PENANAMAN NILAI MORAL DAN SIKAP TOLERANSI BAGI KELUARGA BEDA AGAMA - Relit Nur Edi; Rifandy Ritonga; Isharyanto Isharyanto; Aan Suhendri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Moral values ​​and tolerance for families of different religions are the foundation in the most important efforts to maintain harmony in the family. Working together in doing good without differentiating the type of religion is a way to increase and strengthen harmony. The purpose of this study was to determine the factors that trigger religious differences in the family, to determine the inculcation of moral values ​​in children in different religious families and to determine the tolerance attitude of society in families in which have different religions. This research uses field research, using a qualitative descriptive approach, which is to clearly describe events in the form of moral inculcation and tolerance for families of different religions through the interview process. Factors that trigger religious differences in families due to interfaith marriages and interfaith families due to changing religions. The inculcation of children's moral values ​​in families of different religions includes: religiosity, discipline and morals. The attitude of tolerance in the community applies an attitude of tolerance to families of different religions including: freedom of religion, respect for different religions, and agreeing with religious differences. All types of applications carried out by the community have an attitude of tolerance.